Acinetobacter baumannii in suspected bacterial infections: Association between multidrug resistance, virulence genes, & biofilm production - Deepan Gautam; Karma Gurmey Dolma; Bidita Khandelwal; Ramesh Kumar Goyal; Watcharapong Mitsuwan; Maria de Lourdes Pereira; Wiyada Kwanhian Klangbud; Madhu Gupta; Polrat Wilairatana; Abolghasem Siyadatpanah; Christophe Wiart; Veeranoot Nissap (Indian Council of Medical Research, 2023)
Background & objectives: Acinetobacter baumannii has emerged as a nosocomial pathogen with a tendency of high antibiotic resistance and biofilm production. This study aimed to determine the occurrence of A. baumannii from different clinical specimens of suspected bacterial infections and furthermore to see the association of biofilm production with multidrug resistance and expression of virulence factor genes in A. baumannii. Methods: A. baumannii was confirmed in clinical specimens by the detection of the blaOXA-51-like gene. Biofilm production was tested by microtitre plate assay and virulence genes were detected by real-time PCR. Results: A. baumannii was isolated from a total of 307 clinical specimens. The isolate which showed the highest number of A. baumannii was an endotracheal tube specimen (44.95%), then sputum (19.54%), followed by pus (17.26%), urine (7.49%) and blood (5.86%), and <2 per cent from body fluids, catheter-tips and urogenital specimens. A resistance rate of 70-81.43 per cent against all antibiotics tested, except colistin and tigecycline, was noted, and 242 (78.82%) isolates were multidrug-resistant (MDR). Biofilm was detected in 205 (66.78%) with a distribution of 54.1 per cent weak, 10.42 per cent medium and 2.28 per cent strong biofilms. 71.07 per cent of MDR isolates produce biofilm (P<0.05). Amongst virulence factor genes, 281 (91.53%) outer membrane protein A (OmpA) and 98 (31.92%) biofilm-associated protein (Bap) were detected. Amongst 100 carbapenem-resistant A. baumannii, the blaOXA-23-like gene was predominant (96%), the blaOXA-58-like gene (6%) and none harboured the blaOXA-24-like gene. The metallo-β-lactamase genes blaIMP-1 (4%) and blaVIM-1(8%) were detected, and 76 per cent showed the insertion sequence ISAba1. Interpretation & conclusions: The majority of isolates studied were from lower respiratory tract specimens. The high MDR rate and its positive association with biofilm formation indicate the nosocomial distribution of A. baumannii. The biofilm formation and the presence of Bap were not interrelated, indicating that biofilm formation was not regulated by a single factor. The MDR rate and the presence of OmpA and Bap showed a positive association (P<0.05). The isolates co-harbouring different carbapenem resistance genes were the predominant biofilm producers, which will seriously limit the therapeutic options suggesting the need for strict antimicrobial stewardship and molecular surveillance in hospitals.